Strategi Komunikasi Pimpinan Majelis Taklim Surau Al-Hidayah Siman dalam Meningkatkan Keaktifan Jamaah di Kabupaten Natuna Kepulauan Riau - Alfiatul Karima; Hendra Hendra; Alfidelma Nelza; Iwandi Iwandi (Khulasah : Islamic Studies Journal, 2026)
Religious guidance is an important effort to improve the understanding and practice of Islamic teachings within the community. The Majelis Taklim of Surau Al-Hidayah Siman in Natuna Regency, Riau Islands Province, is a non-formal Islamic educational institution that plays an important role in fostering religious life through various religious activities. The success of these activities is closely related to the communication strategies employed by the leaders of the Majelis Taklim to encourage, motivate, and enhance congregation participation. This study aims to analyse the communication strategies employed by the leaders of the Majelis Taklim of Surau Al-Hidayah Siman in increasing congregation participation in Natuna Regency, Riau Islands Province. This study employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The findings reveal that the communication strategies include interpersonal communication, persuasive communication, group communication, and exemplary leadership in building close relationships with the congregation. These strategies have contributed to increasing congregation participation in religious activities despite several challenges, including work commitments, family responsibilities, and limited time.